Pieces of Civic Intelligence: Towards a Capacities Framework. (October 2014) - Schuler, Douglas
Civic intelligence is the capacity of collectivities — from small informal groups to humanity as a whole — to equitably and effectively address important shared problems such as poverty, bioterrorism, and natural disasters. It's an abstract concept that can be expressed in policy, art, demonstrations, or conversation. In this article, civic intelligence has been divided into five main capacities: knowledge, attitude and aspiration, organizational capital, relational and social capital, and financial and material resources. The capacities framework is intended to convey a holistic phenomenon in a relatively simple way. While the framework as it currently exists can be useful in both research and practice, it's undoubtedly not the last word. The capacities framework for civic intelligence is more of a springboard for collaboration and action than a strait jacket that imposes inflexible and unalterable discipline.